Anti-Inflammatory Effects of C-Peptide Prevent Endothelial Dysfunction in Type 1 Diabetes - Cifarelli, Vincenza; Trucco, Massimo; Luppi, Patrizia (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2011)
C-peptide, historically considered a biologically inactive peptide, has been shown to exert insulin-independent biological effects on a number of cells proving itself as a bioactive peptide with anti-inflammatory properties. Type 1 diabetes (T1D) patients typically lack physiological levels of insulin and C-peptide. Recombinant insulin administrations, in the absence of C-peptide, correct hyperglycemia but leave an increased risk of developing microvascular complications affecting the small vessels of the eye, the kidneys, and the peripheral nerves. Inflammation is an important factor for the development of diabetes-associated vascular complications, and there is increasing evidence that T1D patients, even at a young age and after short duration of T1D, have circulating activated monocytes and increased plasma levels of inflammatory cytokines. It has been hypothesized that reduced plasma levels or lack of circulating C-peptide might contribute to the development of diabetes-associated vascular complications since C-peptide is able to reduce the inflammatory response associated with T1D. In this review, we present the most-up-to date information on the anti-inflammatory activity of C-peptide at the level of the vascular endothelium exposed to a variety of glucose levels. The anti-inflammatory properties of C-peptide in animal models of endotoxic shock and T1D-associated encephalopathy are also presented. The present evidence favours the view that T1D should be considered a dual-hormone deficiency disorder and emphasizes the possibility that replacement therapy with both insulin and C-peptide in T1D patients may offer an approach to retard or completely prevent the development of diabetes-associated microvascular complications, for which no causal therapy is available today.
Keywords: complications